Digital learning transformation for civil servants through mooc: An impact study of the pintar self-learning training program by the ministry of religious affairs in maluku and north maluku - Arsyil Waritsman; Rita Lefrida (Balai Diklat Keagamaan Ambon, 2025)
This study aims to analyse the impact of training programs for civil servants (ASN) on two key aspects: first, the implementation of their duties and responsibilities; and second, the improvement of organisational performance and service delivery to stakeholders. The research employed a quantitative method. Data were collected using a non-test technique in the form of a questionnaire. Accordingly, the research instrument was a questionnaire consisting of a list of statements with five alternative answers on a Likert scale. The population consisted of all civil servants from the Ministry of Religious Affairs in Maluku and North Maluku Provinces, while the sample comprised randomly selected civil servants from the same population who served as respondents. The collected data were analysed using descriptive and inferential statistics. Descriptive statistics were used to present the distribution of respondents' data, while inferential statistics were employed in a One-Sample t-test with a 5% significance level. In this context, inferential statistics were used to generalise whether the MOOC Pintar training had a significant impact. The findings reveal that the MOOC Pintar training has a significant impact on civil servants of the Ministry of Religious Affairs in Maluku and North Maluku Provinces. These results underscore the importance of sustaining the MOOC Pintar training continuously, given its significant contribution to improving civil servants' task implementation, positional responsibilities, organisational performance, and stakeholder service. Although this research is limited to the perceptions of civil servants in the two provinces and the impact measured was confined to their self-perceptions, without incorporating supervisors' assessments, the findings nonetheless provide valuable recommendations for future studies in other regions. Further research, including supervisor evaluations, is suggested to broaden the scope of data regarding the impact of MOOC Pintar on civil servants of the Ministry of Religious Affairs.